A Systematic Literature Review: Penerapan Business Intelligence dalam Meningkatkan Pengambilan Keputusan - Lailaturahma Maulidah; Nadin Isna Monica; Putri Nurul Hidayati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The development of a company or organization is greatly influenced by the significant role of Management Information Systems. The performance of information systems in an organization determines the success of the organization in the fierce market competition of this era. In the application of information system technology, there is BI (Business Intelligence) as a tool used to help a company run modern management. However, not all technologies provide added value to the company. The purpose of this research is none other than to review the advantages of using BI in organizational management used to improve decision making. In this research, the Systematic Literature Review (SLR) method is used which aims to conduct a comprehensive analysis, review, evaluation, and interpretation of all relevant studies on phenomena related to the specific research questions. The results of this study include or cover several areas that are targeted for Business Intelligence implementation, especially in the industrial sector. The implementation of Business intelligence also requires a clear framework to be used later as a decision-making tool. In addition, the implementation of BI in an organization certainly has challenges such as managing company data, utilizing company data, and also making good and appropriate decisions.